2021
DOI: 10.3390/metabo11050298
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microbiome and Microbiota-Derived Sodium Butyrate on Drosophila Transcriptome and Metabolome Revealed by Multi-Omics Analysis

Abstract: The host microbiome plays an important role in regulating physiology through microbiota-derived metabolites during host-microbiome interactions. However, molecular mechanism underly host-microbiome interactions remains to be explored. In this study, we used Drosophila as the model to investigate the influence of microbiome and microbiota-derived metabolite sodium butyrate on host transcriptome and metabolome. We established both a sterile Drosophila model and a conventional Drosophila model to demonstrate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Gut microbes play important roles in insect growth, development, and many physiological processes of the individual to maintain host health through regulating gene expression ( Raymann et al, 2017 ; Schoeler and Caesar, 2019 ; Zhou et al, 2021 ). It has been shown that gut microbes are important in absorbing nutrition, protection from parasites and pathogens, modulation of immune responses, and communications with environment ( Engel and Moran, 2013 ; Jang and Kikuchi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbes play important roles in insect growth, development, and many physiological processes of the individual to maintain host health through regulating gene expression ( Raymann et al, 2017 ; Schoeler and Caesar, 2019 ; Zhou et al, 2021 ). It has been shown that gut microbes are important in absorbing nutrition, protection from parasites and pathogens, modulation of immune responses, and communications with environment ( Engel and Moran, 2013 ; Jang and Kikuchi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dysbiosis of intestinal microbes can affect the metabolic process. In Drosophila , we have demonstrated the impact of microbiome and microbiota-derived sodium butyrate on host transcriptome and metabolome with multi-omics data ( Zhou et al, 2021 ). Our studies revealed that the changes in composition and diversity of insect’s gut microbial community can influence important physiological functions in the host through regulating gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial DNA was purified using the TIANamp Bacteria DNA kit (Tiangen Biotech Inc., Beijing, China), following the manufacturer’s protocols. A region encompassing the V3–V4 hypervariable regions of the 16S rRNA gene was amplified using the primers 341F (CCTACGGGNGGCWGCAG) and 806R (GGACTACHVGGGTATCTAAT) ( 52 ). The PCR amplification system comprehended 20 μL, including 10 μL premixed Taq (Takara), 1 μL of each primer (10 μM), 2 μL gDNA, and 6 μL ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…Epithelial injury causing exposure of crypt ISCs to butyrate suppresses ISC proliferation and mucosal wound healing via Foxo3 regulation [113]. In Drosophila, the addition of sodium butyrate in the diet can effectively extend viability and life span [114] and microbiota-derived sodium butyrate impacts the microbiota composition and host gene expression [115]. Sodium butyrate was found to induce Firmicutes and to suppress Proteobacteria, while at the gene expression level, it was shown to have an inhibitory effect in key biological processes such as cell proliferation [115].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%